KINERjA WANITA NELAYAN DALAM INDUSTRI RUMAH TANGGA STUDI SOSIAL – EKONOMI MASYARAKAT KOTA SEMARANG - Muji Utami, Santi (Forum Ilmu Sosial, 2009)
In dealing with employment opportunities for women, empowerment of economic institutions that are ooted in the community such as domestic industry is a perfect alternative. for its activities in the vicinity f the home (home - base - production), in their own homes and independent businesses. The writing was trying to describe the basic capabilities of women fshing, types of household industries, fshing her ontribution to the family economy, and the constraint factor in obtaining women fshing opportunities n domestic industrial sector The method used in this study are qualitative methods using techniques Trianggulasi. Analysis of ata using an interactive model analysis The research subject is women who are living in a fshing village, ocated in the productive age status as wives or widows who became head of the family, Based on the results and discussion can be concluded that the skills / basic skills that most women re based on the experience of fshermen who by his predecessors. The wives of fshermen do the work n the household sector in the form of marinating, smoking and making Pindang. They also perform other obs in general are associated with fshing activities. The fsher women who work at this informal sector, will increase the household fnances because her husband’s income level was not suffcient fulfllment of aily life. Women who are involved fshermen earning activities are active actors socio-economic changes n fshing communities. Factors that hamper the performance of women in the household industry sector s the low motivation to develop business, education level is relatively low, and limited capital, ability nd skills possessed.Keywords: Seconds merchant, peoples economic, entrepreuneurship